Mahkamah Konstitusi sebagai Negatif Legislator: Analisis Peran dan Batasan dalam Pembatalan Undang-Undang - Irwan, Muhamad; Saleh, Moh. (Legal Standing : Jurnal Ilmu Hukum, 2025)
The Constitutional Court of Indonesia holds a significant position as a negative legislator, primarily tasked with reviewing laws for their alignment with the 1945 Constitution. This research explores the scope of the court’s authority and its constraints, particularly when nullifying laws or inadvertently establishing new legal norms. Through a normative legal approach, this study investigates several rulings of the Constitutional Court to evaluate whether the court surpasses its jurisdiction by creating new legal precedents. The findings underscore an ongoing discussion about whether the court maintains its role within the separation of powers or encroaches upon the legislative domain. The study concludes with assessing the legal consequences of these rulings and their broader influence on Indonesia's legal and governance systems.